PENGEMBANGAN ORGANISASI KECAMATAN DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH DI KECAMATAN TENGGARONG, KABUPATEN KUTAI KARTANEGARA - Margono . (Jurnal Paradigma (JP), 2017)
The main purpose of this research is to describe and to analyze the development of subdistrict organization in implementing the local government. At the same time it also tries to seek the support factors and obstacles in developing the subdistrict organization. The research focus is about the effectivity of subdistrict organization in Kutai Kartanegara district covering flexibility, human development, productivity, control. The research findings indicate that the development of subdistrict organization did not run well, it can be seen from four aspects above.